Extended-spectrum β-lactamase- and AmpC β-lactamase-producing Enterobacterales associated with urinary tract infections in the New Zealand community: a case-control study. (March 2023) - Toombs-Ruane, Leah J.; Marshall, Jonathan C.; Benschop, Jackie; Drinković, Dragana; Midwinter, Anne C.; Biggs, Patrick J.; Grange, Zoë; Baker, Michael G.; Douwes, Jeroen; Roberts, Mick G.; French, Nigel P.; Burgess, Sara A.
Highlights: No pet factor was found associated with extended-spectrum β-lactamase-/ AmpC β-lactamase-producing Enterobacterales urinary tract infection. Risk factors included overseas travel, previous antibiotic use, and medical contact. ST131 was the dominant sequence type among clinical isolates. Genomic analysis of extended-spectrum β-lactamase-producing Escherichia coli suggested intercommunity transmission. Abstract: Objectives: To assess whether having a pet in the home is a risk factor for community-acquired urinary tract infections associated with extended-spectrum β-lactamase (ESBL)- or AmpC β-lactamase (ACBL)- producing Enterobacterales. Methods: An unmatched case-control study was conducted between August 2015 and September 2017. Cases (n = 141) were people with community-acquired urinary tract infection (UTI) caused by ESBL- or ACBL-producing Enterobacterales. Controls (n = 525) were recruited from the community. A telephone questionnaire on pet ownership and other factors was administered, and associations were assessed using logistic regression. Results: Pet ownership was not associated with ESBL- or ACBL-producing Enterobacterales-related human UTIs. A positive association was observed for recent antimicrobial treatment, travel to Asia in the previous year, and a doctor's visit in the last 6 months. Among isolates with an ESBL-/ACBL-producing phenotype, 126/134 (94%) were Escherichia coli, with sequence type 131 being the most common (47/126). Conclusions: Companion animals in the home were not found to be associated with ESBL- or ACBL-producing Enterobacterales-related community-acquired UTIs in New Zealand. Risk factors included overseas travel, recent antibiotic use, and doctor visits.